Post-operatory respiratory insufficiency - Bertullo, Hugo; Mazza, Norma; Correa, Humberto; Ibarbouru, Osvaldo (Cirugía del Uruguay, 1978)
Retrospective review of a series of fifty patients suffering from po'st-operatory respiratory insufficiency (PRI) treated in the Intensive Care Unit of the Hospital de Clínicas (University Hospital) of Montevideo. The highest incidence of respiratory failure is found in patientes in their fifties and sixties, regardless of sex and generally after urgency surgery in the supra mesocolic compartment. As a consequence of studying the gasses contained in the blood, patients can be divided into two groups with well-defined gaso'metric profiles: Group 1 - hypoxia and hypocapnia Group 2 - hypoxia and hypercapnia Causes, physio'pathology, evolution and treatment of both groups are discussed, with emphasis of the importance of an early treatment of intra-abdominal septic foci and o'n supporting measures, fundamentally.